2023
DOI: 10.1021/acs.inorgchem.2c04393
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of the Fe(III)-Tiron System in Solution through an Integrated Approach Combining NMR Relaxometric, Thermodynamic, Kinetic, and Computational Data

Abstract: The Fe(III)-Tiron system (Tiron = 4,5-dihydroxy-1,3-benzenedisulfonate) was investigated using a combination of 1 H and 17 O NMR relaxometric studies at variable field and temperature and theoretical calculations at the DFT and NEVPT2 levels. These studies require a detailed knowledge of the speciation in aqueous solution at different pH values. This was achieved using potentiometric and spectrophotometric titrations, which afforded the thermodynamic equilibrium constants characterizing the Fe(III)-Tiron syste… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 50 publications
(112 reference statements)
1
4
0
Order By: Relevance
“…As reported by Nucera et al 30 and Charkoudian et al , 37 Fe( iii )-catechol (Cat) type complexes demonstrated pH-dependent coordination equilibria, existing as mono-, bis-, and tris-Cat coordination forms with different Fe( iii )-hydrated states ([Fe(Cat) x (H 2 O) 6−2 x ], x = 1, 2, 3) when the pH varied from acidic to alkaline values. In this work, as shown in Fig.…”
Section: Resultssupporting
confidence: 57%
See 2 more Smart Citations
“…As reported by Nucera et al 30 and Charkoudian et al , 37 Fe( iii )-catechol (Cat) type complexes demonstrated pH-dependent coordination equilibria, existing as mono-, bis-, and tris-Cat coordination forms with different Fe( iii )-hydrated states ([Fe(Cat) x (H 2 O) 6−2 x ], x = 1, 2, 3) when the pH varied from acidic to alkaline values. In this work, as shown in Fig.…”
Section: Resultssupporting
confidence: 57%
“…As shown in Chart 2, the ditopic ligand (L) derived from L-Dopa contains an EDTA moiety and a catechol group, serving as the complexing unit for the Mn(II) ion and transition metal ions (M = Ti 4+ or Fe 3+ ), respectively. Additionally, as demonstrated in precedent studies like in the Fe(III)-Tiron system, 30 the Fe(III)-catechol core can provide a relatively intense and broad absorption band in the visible to near-infrared (NIR) region due to ligand-to-metal charge transfer (LMCT) and ligand-localized p-p* electronic transitions, providing this Mn(II)-metallostar with potential for NIRresponsive phototherapy properties.…”
Section: Papermentioning
confidence: 99%
See 1 more Smart Citation
“…The rotational correlation time, τ R 298 , has a value which corresponds to the size of the complex. We note that the scalar coupling constant has a negative sign in the formalism of the Solomon‐Bloembergen‐Morgan equations used (supporting information), although it should be theoretically positive as the consequence of a negative spin density at the oxygen nucleus and the negative magnetic moment of the 17 O nucleus, as it was demonstrated by different authors [45–46] . The electron spin relaxation is notably faster for GdL2 than for GdDOTA , as expressed by its seven times higher Δ 2 value (Table 6).…”
Section: Resultsmentioning
confidence: 51%
“…2,3 However, the development of Fe(III) MRI probes has received more attention over the past few years. [4][5][6][7][8][9][10][11] A motivation for the development of iron MRI probes is to take advantage of the biochemical mechanisms in animals as well as humans to sequester and store excess iron. [12][13][14] However, ligands designed for Fe(III) chelation need to take into account the unique chemistry of the highly Lewis acidic and small-sized Fe(III) ion.…”
Section: Introductionmentioning
confidence: 99%